Penerapan Permainan Gebrakan Dengan Kartu Bilangan Bulat Sebagai Media Pembelajaran Pada Pembelajaran Matematika - Mohamad Yudiyanto; Deni Soidin; Suhara, Djenal; Martini, Susi (Prodi PGMI STAI Sabili Bandung, 2023)
This research was conducted to see that there was a significant influence in the teaching and learning process in mathematics, beside that we want to produce fun learning media. To get good quality learning media in the learning process, it is necessary to choose and plan the use of appropriate and effective learning media. Departing from these problems the researcher tried to apply a breakthrough game learning media using integer cards. Research methods using observation and library research. Based on the result of data analysis and direct observation, that the use off buzz games using integer cards as learning media in mathematics can be applied in accordance with the design and material presented. Beside that SK (competency standard) and KD (Basic Competence) mathematics subject matter of integers were achieved, judging by the indicators that both groups were able to operate integer correctly.